2009
DOI: 10.1007/s00586-009-1229-9
|View full text |Cite
|
Sign up to set email alerts
|

Does an interspinous device (Coflex™) improve the outcome of decompressive surgery in lumbar spinal stenosis? One-year follow up of a prospective case control study of 60 patients

Abstract: A number of interspinous process devices have recently been introduced to the lumbar spinal market as an alternative to conventional surgical procedures in the treatment of symptomatic lumbar stenosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
44
2
5

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 81 publications
(59 citation statements)
references
References 17 publications
8
44
2
5
Order By: Relevance
“…While the research group was planning to perform a randomized controlled trial (RCT), such a prospective comparative study of this implant is not available in Pubmed. After the introduction of this implant by Senegas, the development of other IPDs followed, such as Minns, X-stop and Coflex [13][14][15][16]. Cadaveric studies did not show any biomechanical difference between the various IPDs, and they were therefore considered as interchangeable, although differences in clinical effectiveness were not investigated [15].…”
Section: Interspinous Process Devices Versus Microdecompressionmentioning
confidence: 99%
“…While the research group was planning to perform a randomized controlled trial (RCT), such a prospective comparative study of this implant is not available in Pubmed. After the introduction of this implant by Senegas, the development of other IPDs followed, such as Minns, X-stop and Coflex [13][14][15][16]. Cadaveric studies did not show any biomechanical difference between the various IPDs, and they were therefore considered as interchangeable, although differences in clinical effectiveness were not investigated [15].…”
Section: Interspinous Process Devices Versus Microdecompressionmentioning
confidence: 99%
“…There were no late neurological complications related to the device and no cases of Coflex penetration inside the canal or infection. Richter et al reported 3.3 % hardware related complications (spinal process fracture and prosthesis loosening) in 2010 [7]. An international multicenter retrospective study [23] that included 209 patients who underwent Coflex fixation surgery reported a 3.4 % device-related complication rate, most of which were fixed-wing breakage and prosthesis loosening.…”
Section: Coflex Device-related Complicationsmentioning
confidence: 99%
“…Furthermore, there is some evidence that fusion may increase the biomechanical stresses imposed on the adjacent segments leading to transitional diseases [1][2][3], and may be related to other problems such as serious trauma, transfusion requirement, higher morbidity and mortality for elderly patients as well as pseudarthrosis and fusion mass fracture [4,5]. In order to overcome these deficiencies associated with fusion surgery, the interspinous process device-Coflex system (Paradigm Spine Inc.®, Germany) was developed as a possible alternative to spinal decompression with a posterolateral fusion and instrumentation for the treatment of symptomatic degenerative lumbar disease including mild segmental instability, degenerative disc disease, and lumbar spinal stenosis [6,7]. Recently, the encouraging results of Coflex have been widely reported.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Basing upon strong research and clinical evidences, the X-STOP device has been recognized as having a role in the surgical treatment of lumbar spinal stenosis causing Neurogenic Intermittent Claudication (NIC), particularly if compared with non-operative therapy and decompressive surgery [3]. The Coflex U-shaped titanium implant has been used in same clinical scenarios [4] and in its latest version it is used as an adjunct to interbody fusion.…”
Section: Introductionmentioning
confidence: 99%